2004
DOI: 10.1111/j.0143-2885.2004.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

C‐shaped root canals of mandibular second molars in a Korean population: clinical observation and in vitro analysis

Abstract: There was high prevalence of C-shaped root canals in the mandibular second molars of Koreans. C-shaped canals having semicolon and continuous shapes at the canal orifice have a high possibility of being divided into two or three canals in the apical region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
92
2
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 14 publications
(15 reference statements)
11
92
2
4
Order By: Relevance
“…13,14,18 The Chinese population also presented high prevalence of C-shaped canals, as reported by Yang et al, 12 Zheng et al 20 and Zhang et al 5 (32%, 39% and 29%, respectively). C-shaped root and canal configurations were seldom found in Caucasian populations: Cooke and Cox, 1 Weine 7 and Cimilli et al 8 reported a prevalence of 2.7%, 7.6% and 8.1% of C-shaped canals, respectively.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…13,14,18 The Chinese population also presented high prevalence of C-shaped canals, as reported by Yang et al, 12 Zheng et al 20 and Zhang et al 5 (32%, 39% and 29%, respectively). C-shaped root and canal configurations were seldom found in Caucasian populations: Cooke and Cox, 1 Weine 7 and Cimilli et al 8 reported a prevalence of 2.7%, 7.6% and 8.1% of C-shaped canals, respectively.…”
Section: Discussionsupporting
confidence: 56%
“…13,14 A study recently conducted in the Brazilian population evaluated the root canal configuration of mandibular molars, and showed that the prevalence of C-shaped canals in second molars was 3.5%; however, the authors did not report the characteristics of its configuration, bearing in mind that the study was not limited to evaluating only the Cshaped canals. 15 Therefore, the aim of this study was to use CBCT images to evaluate the prevalence and configurations of C-shaped canals in the permanent mandibular second molars of members of a Brazilian subpopulation.…”
Section: Andmentioning
confidence: 99%
“…Standard radiography can provide only two-dimensional images for three-dimensional objects and can only show main canals along the root, with a low probability of showing the extent of the complexities of root canal systems, for additional root canals can be missed on the radiograph (Al Nazhan 1999). To visualize the buccolingual anatomy with greater accuracy, two preoperative radiographs are made: one with a 90° angulation to the tooth in a buccolingual direction and a second at a mesial angle of approximately 20° (Seo and Park 2004). The direct digital radiography (DDR) system is now in operation clinically and, as an addition to alternative radiographic documentation, offers more benefits than conventional radiography.…”
Section: Methods Of Root Canal System Detectionmentioning
confidence: 99%
“…The prevalence of C-shaped canals in Koreans has been reported to be as high as 32.7% and this variation is most frequently found in the mandibular second molar [9]. Although studies have reported RE or C-shaped root canals in mandibular molars, few studies have investigated the Cshaped root canal in mandibular first molar with RE [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Gemination and fusion are similar developmental anomalies of hard tissues with a different etiology [9]. Fusion is the union of hard tissue between two developing teeth.…”
Section: Introductionmentioning
confidence: 99%